Online helpdesk for Maybank account payable system (MAPS) - Raman Nair, Shobani (2005)
The aim of this project is to develop a web-based Online Helpdesk for Maybank Account Payable System. Maybank Account Payable System (MAPS) is a system currently used in Maybank to make payments to third party vendors on product and services obtained by Maybank. The users of the system will be users from Property and ISD Department in Maybank. Currently when the system users face a problem with MAPS system, there is no tool or system used to log the problem to the IT Technical Supports. The users will log the problem in a manual method by making a phone call to the IT Technical Support. Besides that, the management is also facing difficulties because there is no proper tracking to problems raised by users. The management is also facing difficulties to gauge the performance of the IT Technical Support, because the support provided is not documented within the organization. Thus, Online Helpdesk for Maybank Account Payable System is designed specifically to address the problems mentioned above. The system will automate the manual process of logging a problem to the IT Technical Support via the web-based system. With the system, there will be a proper control over the problem logged because there is an escalation process. The system will be able to determine whether a problem is resolved within the time frame allocated or better known as SLA (Service Level Agreement) timing. When the IT Technical Support closes a case, a PDF format report will be generated for the view of the IT Manager. The report will log the time the case is opened and closed. The report will also indicate whether the case has been closed within the agreed time. With this report, the IT Manager will be able to gauge the performance of the IT Technical Support and will be able to make fair decision during the KPI review